Update of the Xylella spp. host plant database – systematic literature search up to 30 June 2021 - European Food Safety Authority (EFSA); Alice Delbianco; Davide Gibin; Luca Pasinato; Massimiliano Morelli (EFSA Journal, 2022)
Abstract Following a request from the European Commission, EFSA was asked to create and regularly update a database of host plant species of Xylella spp. The mandate now covers the period 2021–2026 and EFSA is requested to release an update of the database twice per year. The aim of the database is to provide information and scientific support to risk assessors, risk managers and researchers dealing with Xylella spp. This report is related to the fifth version of the database published in Zenodo in the EFSA Knowledge Junction community, covering literature published from 1 January 2021 up to 30 June 2021, and recent Europhyt outbreak notifications. Informative data have been extracted from 41 selected publications. Nineteen new host plants were identified and added to the database since the previous update published in June 2021. Those plant species were reported naturally infected by subsp. multiplex or unknown (i.e. not reported in the publication) of X. fastidiosa in the UE (France, Spain and Portugal). No additional data were retrieved for X. taiwanensis. New information on the tolerant/resistant response of plant species to X. fastidiosa infection were added, while no new STs have been identified worldwide compared to the previous update published in May 2021. The overall number of Xylella spp. host plants determined with at least two different detection methods or positive with one method (between: sequencing, pure culture isolation) now reaches 407 plant species, 185 genera and 68 families. Such numbers raise to 655 plant species, 293 genera and 88 families if considered regardless of the detection method applied.